2018
DOI: 10.1108/ijem-08-2017-0193
|View full text |Cite
|
Sign up to set email alerts
|

Tacit knowledge-sharing behavior among the academic staff

Abstract: Purpose The purpose of this paper is to examine the critical success factor of tacit knowledge-sharing behavior among the academic staff of higher learning institutions. Design/methodology/approach A total of 200 questionnaires were distributed among the academic staff of higher learning institutions in Bangladesh. Collectively, 150 usable responses were returned. Apart from descriptive statistics, this research applied confirmatory factor analysis (CFA) and structural equation modeling (SEM) to assess the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
25
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 120 publications
(128 reference statements)
8
25
2
Order By: Relevance
“…Besser and Shackelford (2007) stated that individuals with high extroversion trait of personality are inclined to be more sociable. Past studies revealed that extrovert individuals are energetic, enthusiastic and optimistic (Farrukh et al, 2016;Rahman et al, 2018a). It is advocated that extroverts have positive emotions and they contribute a great number of efforts for the satisfaction of team (Barrick et al, 1998;McCrae, 1996;Watson et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Besser and Shackelford (2007) stated that individuals with high extroversion trait of personality are inclined to be more sociable. Past studies revealed that extrovert individuals are energetic, enthusiastic and optimistic (Farrukh et al, 2016;Rahman et al, 2018a). It is advocated that extroverts have positive emotions and they contribute a great number of efforts for the satisfaction of team (Barrick et al, 1998;McCrae, 1996;Watson et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In the normative dimension, the items were related to office governance principles that prioritize moral principles, working earlier, preparing everything based on the main virtues' awareness as organizational ethics. To measure tacit knowledge sharing, Cummings (2004) Rahman et al (2018) scale was adopted, which comprised of sharing information with colleagues, involving myself in online discussions on various research How to encourage lecturer performance in research through servant leadership, organizational commitment, and tacit knowledge sharing 39 topics, spending time doing knowledge sharing activities online in my team to share personal experiences, share information with other lecturers even though he is not in the same department, involve himself in discussions on various technical topics with colleagues from different work teams using multiple online technologies for research Measurement of research performance was developed based on Winarno & Hermana (2019), Sukirno (2020), namely quality, quantity and adding delivery time which shows the response and proactive behavior of lecturers in conducting research. The number of research results includes the number of international, Scopus-and non-Scopus indexed the last five years, number of national journals, participation in conferences, and number of research proposals funded by the institution / Ministry / foreign donor in the previous five years.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have investigated the management of tacit knowledge in different environments. Rahman et al (2018) investigated tacit knowledge-sharing behaviour amongst the academic staff of higher learning institutions and found that personality traits affect tacit knowledgesharing behaviour amongst the academic staff of higher learning institutions, except for conscientiousness personality trait. Their study is almost similar to the current study, the difference being the context in which the two studies were conducted.…”
Section: Related Studiesmentioning
confidence: 99%